(untitled) (Homiletic, 2018)
This article reflects on the challenges and importance of extended, global homiletic conversations. Drawing on my experience as a Westerner teaching preaching in the Pacific, the article asserts the necessity of global homiletic conversation as a guard against hegemonic preaching practices and as a productive agent of cultural destabilization. This is particularly true when defining the contours of postcolonial preaching. By moving preaching into postures of Spirit-dependence similar to Mary’s dependence on the Spirit in Luke’s gospel, global homiletic conversation can facilitate sacramental performances of embodied relation between preachers, their changing communities, and Christ.